Persepsi Guru Matematika dalam Penggunaan Media Manipulatif Materi Perbandingan pada Karakter Siswa - Imron Fauzi; Frisa Dewi Mardarani; Agustian Anggraeni; Muhammad Usamah; Karmila Utami (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
In the learning process, the teacher has an obligation to be able to share attention and supervision to students, especially in using manipulative materials. Giving more supervision by the teacher in the use of manipulative materials is very necessary. In this study, has the aim of knowing the perception of mathematics teachers in the use of manipulative mathematics teaching materials with comperative material on students to improve character. Any research that uses descriptive qualitative methods from the perception through mathematics teachers which produces research data with a very good response. Research results by showing thatÂ  perception by mathematics teachers in the use of manipulative mathematics teaching materials for comparison materials resulted that use through manipulative teaching materials was very effective if used on comparative materials for students to improve their character. It is indicated by the perception achieved by the teacher towards the students. So that learning using manipulative materials needs to be considered by educators to be more focused so that learning runs more optimally.